PENGENDALIAN BIAYA DAN JADUAL TERPADU PADA PROYEK KONSTRUKSI - Ahmad Ridwan; Rekso Ajiono (U Karst, 2017)
The main resources limited to the stage of implementing a construction project are cost, quality and time. Planning, scheduling and controlling are important steps to take in order to achieve the project's objectives with limited resources. The "Eaned Value" method is a method of control used to control project costs and schedules in an integrated manner. This method provides information on the status of project performance in a reporting period and provides information on the predicted costs required and time to complete all work based on performance indicators when reporting. In the Construction of the Hospital Medical Rehabilitation Installation Building. Overview of Kediri, the information obtained when reporting on the 91st day was Planed Value / PV = Rp 1.4325 billion, Earned Value / EV = Rp.1,3747 and Actual Cost / AC=Rp.1,3598 billion. At present the project performance in terms of cost is said to be profitable (Cost Variant / CV = + Rp. 0.01 billion and Cost Performed Index / CPI = 1.01> 1). From the schedule aspect, it is said that this project is experiencing delays (Schedule Variant / SV = -Rp.0.06 billion and Schedule Performance Index / SPI = 0.96 <1). The predicted cost needed to complete all work is Rp. 2.8683 billion, showing a profit (under a budget plan of Rp. 2.8998 billion). While the prediction schedule required 129 days, showed experiencing a delay of 2 days from the plan.AbstrakSumberdaya utama terbatas pada tahap pelaksanaan suatu proyek kostruksi adalah biaya, mutu dan waktu. Perencanaan, penjadualan dan pengendalian adalah langkah penting untuk dilakukan agar tujuan pelaksanaan proyek dengan sumberdaya terbatas ini tercapai. Metode â€Nilai Hasilâ€ (Eaned Value) adalah sutau metode pengendalian yang digunakan untuk mengendalikan biaya dan jadual proyek secara terpadu. Metode ini memberikan informasi status kinerja proyek pada suatu periode pelaporan dan memberikan informasi prediksi biaya yang dibutuhkan dan waktu untuk penyelesaian seluruh pekerjaan berdasarkan indikator kinerja saat pelaporan. Pada Pembangunan Gedung Instalasi Rehabilitasi Medik RS. Gambiran Kediri, informasi yang didapat saat pelaporan pada hari ke-91 adalah Planed Value/ PV=Rp 1,4325 milyar, Earned Value/ EV=Rp.1,3747 dan Actual Cost /AC=Rp.1,3598 milyar. Pada saat ini kinerja proyek dari aspek biaya dikatakan untung (Cost Varian/ CV= + Rp. 0.01 milyar dan Cost Performed Index /CPI=1,01>1). Dari aspek jadual, dikatakan proyek ini mengalami keterlambatan (Schedule Varian /SV= -Rp.0,06 milyar dan Schedule Performance Indek/SPI=0,96 <1). Prediksi biaya yang diperlukan untuk menyelesaikan seluruh pekerjaan adalah Rp. 2,8683 milyar, menunjukkan mendapat keuntungan (dibawah rencana anggaran Rp. 2,8998 milyar). Sedangkan prediksi jadual yang diperlukan 129 hari, menunjukkan mengalami keterlambatan 2 hari dari rencana.